2022
DOI: 10.3390/ijerph191912351
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Indirect Death Surveillance System of The Great East Japan Earthquake and Tsunami

Abstract: The long-term mortality risk of natural disasters is a key threat to disaster resilience improvement, yet an authoritative certification and a reliable surveillance system are, unfortunately, yet to be established in many countries. This study aimed to clarify the mechanism of post-disaster indirect deaths in Japan, to improve the existing disaster recovery evaluation system and support decision making in public policy. This study first investigated the definition of indirect deaths via a literature review bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Li et al [8] proposed a rapid estimation method of earthquake fatality by combining physical simulations and empirical statistics in China. Zheng et al [9] studied excess mortality of indirect deaths caused by the Great East Japan Earthquake and Tsunami in 2011 and found that the government underreported indirect deaths. Indirect deaths are caused by factors indirectly related to disasters, such as illness deterioration due to difficult conditions while evacuating, increased stress due to drastic changes in living conditions, and suicides among evacuees.…”
Section: Risk and Damage Assessment To Mitigate Damagementioning
confidence: 99%
“…Li et al [8] proposed a rapid estimation method of earthquake fatality by combining physical simulations and empirical statistics in China. Zheng et al [9] studied excess mortality of indirect deaths caused by the Great East Japan Earthquake and Tsunami in 2011 and found that the government underreported indirect deaths. Indirect deaths are caused by factors indirectly related to disasters, such as illness deterioration due to difficult conditions while evacuating, increased stress due to drastic changes in living conditions, and suicides among evacuees.…”
Section: Risk and Damage Assessment To Mitigate Damagementioning
confidence: 99%
“…With enough data on earthquake events, these methods enable an accurate prognosis of seismicity with the aim of mitigating hazard risks [7,8]. Early detection of seismic risks can be solved by evaluating and visualizing different geophysical determinants that affect disaster fatalities at the country level, namely, seismic hazard strength, population density, distribution of locations, demographic and socioeconomic data, ands geological background layers [9][10][11][12]. For instance, a systematic examination of the correlations and links among various geophysical and geological determinants underlying disasters is useful for the prevention of socioeconomic risks in geologically unstable zones [13,14].…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%